A new method for estimating multi-source water supply considering joint probability distributions under uncertainty - Wei, Chenxi; Wang, Xuan; Fang, Jiajia; Wang, Zhijing; Li, Chunhui; Liu, Qiang; Yu, Jingzhi (Frontiers in Earth Science, 2023)
A new method integrating techniques of copula and interval estimation to estimate multi-source water supply was proposed. Using the copula theory, joint probability distributions of multiple water sources were constructed for the estimation of water supply. In addition, the interval estimation was used to obtain the interval of water supply under uncertainty for the formulation of water diversion strategies and the efficient allocation of water resources. This method can give an in-depth investigation on correlations and synchronous-asynchronous characteristics of runoff variations for multiple water sources, thus solving the uncertainty problem of water supply. To demonstrate its applicability, the method was applied to a case study in the Xiong’an New Area, a future metropolis in North China. The results showed that Lognormal distribution for the marginal distributions of source 2 (i.e., the Water Diversion Project from the Yellow River to Baiyangdian Lake) and source 3 (i.e., the South-to-North Water Diversion Project) were feasible. The combined channel source, composed of source 2 and source 3, provided [5.20, 12.10] ×108 m3; and reservoir source provided [0.76, 3.60] ×108 m³ of water resources to the Xiong’an New Area per year. Besides, without the implementation of multi-source combined water supply pattern in the Xiong’an New Area, there would be a large water supply deficit. This research can provide effective practical suggestions and guidance on water resource planning and management.